Consumer sorting and hedonic valuation of wine attributes: exploiting data from a field experiment. (January 2016) - Gustafson, Christopher R.; Lybbert, Travis J.; Sumner, Daniel A.
Abstract: This article uses a novel experimental approach to measure consumer willingness to pay (WTP) for wine attributes. We invited customers of a local supermarket who had selected a bottle of wine to purchase to participate in a valuation experiment. Integrating their original wine choice into the experiment, each participant evaluated six alternative wines, generating a rich set of data on willingness to pay and consumer characteristics. The data from the experiment allow us to compare standard shelf price‐based wine attribute valuation estimates with estimates using WTP data and an increasing amount of information about individual consumers. The full model employs individual fixed effects to estimate WTP parameters without bias from consumer sorting or supply side influences. Our WTP estimates for wine attributes differ markedly from previous attribute value estimates. Consumers in our sample display clear and stable preferences for wine varieties, but less clear preferences for appellations. Our results suggest caution is needed in using market prices to estimate parameters of the consumer valuation function for product attributes.